PENGARUH IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) TERHADAP PENCAPAIAN KINERJA PERUSAHAAN TNT â EXPRESS INDONESIA - Siregar, Alisa Yulima; Samsir, Samsir (Jurnal Tepak Manajemen Bisnis, 2017)
This research is intended to know and analyze 1) the effect of Total QualityManagement (TQM) implementation on employees attachment to PT.TNT - ExpressIndonesia. 2) the influence of Total Quality Management (TQM) implementation oncompany performance at PT.TNT - Express Indonesia. 3) the influence of employeeengagement implementation on company performance at PT.TNT - Express Indonesia.4) the effect of Total Quality Management (TQM) implementation on companyperformance through employee engagement on PT.TNT - Express Indonesia. Thisresearch uses quantitative design. The method used in this research is method. Thepopulation in this study is all employees at the level of managers and supervisors inPT.TNT-Express Indonesia which requires 219 people. Sampling technique in this studyusing proportional random sampling. Determination of the sample using slovin formulawith a precision set at 5%. Thus the sample in this study sampled 142 people at themanager and supervisor level at PT.TNT-Express Indonesia taken at random. Datacompletion techniques in this study using a questionnaire based on the variablesstudied. From the results of the study concluded: 1) the higher total qualitymanagement implementation will be improve the companys employees engangement.2) the higher implementation of quality management executed by managers andsupervisors will improve the performance of the company. 3) the stronger theemployees aengage to the company, the employee will be motivated to run the work andwill have an impact on the performance. 4) the higher the total quality managementimplementation, the companys performance will increase even without the strongengagemnet of the employee.